2017
DOI: 10.1080/15332985.2017.1395778
|View full text |Cite
|
Sign up to set email alerts
|

Helpful support to promote participation in school and work: Subjective experiences of people with mental health problems---A literature review

Abstract: This article provides an overview over current knowledge regarding helpful support to promote participation in education and work among people with mental health problems. Based on 14 studies gleaned from a systematic review, three overarching themes were identified through thematic analysis: Supportive interpersonal relationships, Integrating mental health and everyday life issues with education/employment support, and Person-centred support. The findings call for a deeper understanding of support in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
5
0
2
Order By: Relevance
“…In the second construct, for (H2), psychosocial hazard has a significant effect on safety performance (β = 0.309, t = 4.22, p < 0.000), additionally, in hypothesis (H3), the study found that safety culture impacts on safety performance as well (β = 0.200, t = 2.881, p < 0.004). This result is consistent with findings from several previous research [44,67,117,118]. According to all of these research hypotheses, safety culture has a significant effect on safety performance and psychosocial hazards.…”
Section: Discussionsupporting
confidence: 93%
“…In the second construct, for (H2), psychosocial hazard has a significant effect on safety performance (β = 0.309, t = 4.22, p < 0.000), additionally, in hypothesis (H3), the study found that safety culture impacts on safety performance as well (β = 0.200, t = 2.881, p < 0.004). This result is consistent with findings from several previous research [44,67,117,118]. According to all of these research hypotheses, safety culture has a significant effect on safety performance and psychosocial hazards.…”
Section: Discussionsupporting
confidence: 93%
“…These low rates of work activity may reflect multiple barriers to employment for this population: discrimination from employers (Brouwers et al, 2016; Thornicroft et al, 2009), lower levels of educational attainment (Leach & Butterworth, 2012; Mojtabai et al, 2015), concerns that employment may jeopardize eligibility for public benefits including disability (i.e., Social Security Disability Insurance [SSDI], Supplemental Security Income [SSI]) and health insurance (i.e., Medicaid, Medicare; O’Day, Kleinman, Fischer, Morris, & Blyler, 2017), or the limited ability of employers to accommodate persons with SMI (McDowell & Fossey, 2015). One additional barrier may be the influence of social supports including family members (Sommer, Ness, & Borg, 2018) or service providers (Abraham & Stein, 2009). The research conducted here adds to the body of research about possible barriers to employment among persons with SMI by providing new data from community mental health center clinical and administrative staff in one New England state about their views of employment as a recovery goal for persons with SMI.…”
mentioning
confidence: 99%
“…However, research related to young adults with co-occurring problems shows that they are at risk of experiencing outsiderness [4,12,13]. The group is often associated with various forms of deviations related to psychosocial situations in childhood and adolescence [13][14][15][16], and with low participation in education, work, and other valued activities [12,14]. The terms 'exclusion' and 'inclusion' are used to denote 'objective' measures of membership and participation in 'ordinary' activities as well as subjective dimensions of quality and meaning of life in society [17].…”
Section: Introductionmentioning
confidence: 99%